2022
DOI: 10.1136/bmjgh-2021-007730
|View full text |Cite
|
Sign up to set email alerts
|

Global disparities in public health guidance for the use of COVID-19 vaccines in pregnancy

Abstract: IntroductionGaps in information about the safety and efficacy of COVID-19 vaccines in pregnancy have led to substantial global variation in public health guidance regarding the use of COVID-19 vaccines in pregnancy over the course of the pandemic.MethodsWe conducted systematic screenings of public health authorities’ websites across 224 countries and territories every 3 weeks to track the development of policies on COVID-19 vaccine use in pregnancy. Policies were categorised using a 1–5 permissiveness scale, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…Data on COVID-19 vaccine coverage in pregnancy are scarcely available, even in African countries with permissive policy recommendations [ 35 ]. Although policies regarding COVID-19 vaccine use in pregnancy have evolved over time, imbalances in recommendations between jurisdictions exacerbate prevailing inequities in access and use of COVID-19 vaccines [ 36 ].…”
Section: Barriers To Covid-19 Vaccination Among Pregant Women In Sub-...mentioning
confidence: 99%
“…Data on COVID-19 vaccine coverage in pregnancy are scarcely available, even in African countries with permissive policy recommendations [ 35 ]. Although policies regarding COVID-19 vaccine use in pregnancy have evolved over time, imbalances in recommendations between jurisdictions exacerbate prevailing inequities in access and use of COVID-19 vaccines [ 36 ].…”
Section: Barriers To Covid-19 Vaccination Among Pregant Women In Sub-...mentioning
confidence: 99%
“…A systematic review from the USA showed vaccine acceptance rates ranging from 12-91.4%, which is lowest in Black/African Americans (most of Malawi population were also black), pregnant and breastfeeding women [6] . Low vaccine acceptance among women, especially pregnant and breastfeeding, may be due to a lack of firm and consistent guidance in national policy regarding COVID-19 vaccination [8] . A Nigerian study found that unreliability of clinical trials, safety, and high cost are the main reasons for vaccine hesitancy [9] .…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 , 12 , 13 , 14 , 15 , 16 Recently, the American College of Obstetricians and Gynecologists, the Society for Maternal‐Fetal Medicine, and the Centers for Disease Control and Prevention declared that all pregnant women should be vaccinated to reduce maternal and fetal‐neonatal morbidity and mortality. 17 , 18 However, although it is growingly recognized that COVID‐19 vaccination programs, including booster doses, are safe and open to pregnant women, 19 , 20 Zavala et al 21 observed that, by September 2021, 17% of national policies still continued to recommend against the use of any COVID‐19 vaccine during pregnancy, of which 25% were low‐ and middle‐income countries, taking into consideration the lack of clinical trials, and developmental and reproductive toxicology data involving pregnant women. Moreover, there are still reports of a poor acceptance rate in this category of patients, mainly because of the maternal fear of consequences for fetal‐neonatal health.…”
Section: Introductionmentioning
confidence: 99%